(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Guillain-Barre syndrome (GBS) is an acute frequently severe and fulminating peripheral neuropathy that is autoimmune in nature. It occurs at a rate of between 1 and 4 per 1,00,000 cases annually. In the United States, 5000-6000 cases occur per year. Males are at slightly higher risk of developing GBS than females and in western countries, adults are more frequently affected than children. Objective: This study was carried out to observe the pattern of presentation of GBS among Bangladeshi population. Methods: This is an observational longitudinal study done in Combined Military Hospital (CMH), Bangobandhu Sheikh Mujib Medical University (BSSMU) and National Institute of Neuroscience Hospital (NINS) during the period of January 2010 to June 2012. A total number of 50 GBS patients were included in this study. Results: A total of 50 patients were studied, the mean age of the patients was 30.40± 1.56 and male was found predominant. About 80% of the patients presented with the typical pattern of Landrys are ascending paralysis, 12% had bulbar involvement first and the rest 8% had mixed presentation, 56% patients had facial nerve involvement and 16% patients had bulbar cranial nerve involvement. About 62% patients presented with pain and paresthesia though none had any abnormality in pain, touch and temperature sensation but 10% patients had position sense and 50% had some degree of vibration sense 50 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 abnormality. Ten patients had respiratory muscle weakness requiring Intensive Care Unit (ICU) support. All patients had acute flaccid type of paraplegia or quadriplegia having hyporeflexia or areflexia (mostly). About 56% patients had autonomic involvement but none had sphincter disturbance. On electrophysiology, 56% patients had demyelination type of nerve injury, 36% had mixed and 8% had axonal type of nerve injury. Conclusion: The pattern of presentation of GBS cases was not much variable and was found to be the studies done before. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22923 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014